2010
DOI: 10.1146/annurev.anthro.012809.105113
|View full text |Cite
|
Sign up to set email alerts
|

Defining Behavioral Modernity in the Context of Neandertal and Anatomically Modern Human Populations

Abstract: This review summarizes current thinking about the concept of modern behavior in the context of Neandertals and anatomically modern humans. The decoupling of modern anatomy and modern behavior has prompted researchers to reframe studies of the emergence of modern humans as a debate that explicitly focuses on the origins of behavioral modernity making its intersection with modern anatomy a point of discussion rather than a given. Four questions arise from this debate: (a) What is modern behavior? (b) Is the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 97 publications
2
48
0
11
Order By: Relevance
“…In this way, evolution by natural selection has been extended beyond the vertical genetic inheritance of higher organisms to the oblique and horizontal inheritance common in microbes and generalized to all forms of vertical, Human populations engaging in a suite of complex and symbolic social behaviors that emerged fairly rapidly ;60 000 years ago in Africa as evidenced by major shifts in tool sophistication, diversity, and standardization, personal ornaments, pigments, symbolic inscriptions, a broadening of the subsistence base, increasing settlement and population size, and long-distance trade. Linkage with anatomical or other genetic adaptations remains controversial (Nowell 2010). Anthrome, anthropogenic biome Globally significant ecological patterns produced by sustained direct human interactions with ecosystems (Ellis and Ramankutty 2008).…”
Section: Inclusive Inheritance Cultural Inheritance and The Extendementioning
confidence: 99%
See 2 more Smart Citations
“…In this way, evolution by natural selection has been extended beyond the vertical genetic inheritance of higher organisms to the oblique and horizontal inheritance common in microbes and generalized to all forms of vertical, Human populations engaging in a suite of complex and symbolic social behaviors that emerged fairly rapidly ;60 000 years ago in Africa as evidenced by major shifts in tool sophistication, diversity, and standardization, personal ornaments, pigments, symbolic inscriptions, a broadening of the subsistence base, increasing settlement and population size, and long-distance trade. Linkage with anatomical or other genetic adaptations remains controversial (Nowell 2010). Anthrome, anthropogenic biome Globally significant ecological patterns produced by sustained direct human interactions with ecosystems (Ellis and Ramankutty 2008).…”
Section: Inclusive Inheritance Cultural Inheritance and The Extendementioning
confidence: 99%
“…Yet the role of genetics in explaining the emergence of modern human behaviors ;60 000 years ago in Africa has remained controversial (Henshilwood and Marean 2003, Mellars 2005, Nowell 2010, Fisher and Ridley 2013, Klein 2013, Sterelny 2014. Some experts argue that a genetic mutation or other major genetic change is required to explain the relatively sudden and widespread emergence of the suite of modern human behaviors (Klein 2013), which include symbolic inscriptions, lithic projectile point weapons, personal ornaments, rapid changes in tools and technologies, more highly structured settlements, and long-distance trade (Mellars 2005, Hill et al 2009, Nowell 2010.…”
Section: Human Ultrasociality and The Human Sociocultural Nichementioning
confidence: 99%
See 1 more Smart Citation
“…Trade across social groups, in critical resources such minerals for tool-making and symbolic prestige goods such as shell beads, also emerges at this time (Nowell 2010;Sterelny 2014). We suggest the importance of the latter is that it forms a pre-requisite for enhancing individual, group and community resilience in the face of external shocks that threaten the engineered niche and the challenges of living in complex social groups (Sterelny , 2014Waring et al 2015), and the emergence of human ultrasociality (Hill et al 2009).…”
Section: Humans As Social Network Engineersmentioning
confidence: 93%
“…For these reasons, there has been a proliferation 1 We follow the definition offered by Henshilwood and Marean (2003: 635), that behavioral modernity is "behavior that is mediated by socially constructed patterns of symbolic thinking, actions, and communication that allow for material and information exchange and cultural continuity between and across generations and contemporaneous communities." For some Paleolithic archeologists, the discovery of early symbolic objects in the African MSA and made by Neanderthals in the European Middle Paleolithic has warranted at minimum a clear decoupling of cultural modernity from biological modernity (Nowell 2010), or it has suggested that aspects of behavioral modernity may not be species-specific (d' Errico et al 2001).…”
Section: Introductionmentioning
confidence: 99%